2009
DOI: 10.3382/japr.2008-00049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adding ozone into an intensive broiler production unit on performance, mortality, ammonia levels, and bacterial levels as compared with a non-ozone-treated broiler unit

Abstract: Ozone is a very unstable and reactive molecule that can rapidly oxidize many organic substances and is often used for odor control. It is also known to be an effective biocide at high dose levels. Despite the lack of scientific evidence linking ozone to reduced aerial ammonia at levels that are safe for birds and humans, there is still an interest in the use of the product for commercial production poultry units. The objective of this experiment was to determine the effect of adding atmospheric ozone at a targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Schwean et al 23 also evaluated the effect of adding O 3 (target level of 0.05 ppm) to rooms housing broilers. The authors concluded that the application of this gas in a commercial broiler unit is unacceptable at the dosage studied because of increased mortality and reduced body gain and feed intake.…”
Section: Technical Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Schwean et al 23 also evaluated the effect of adding O 3 (target level of 0.05 ppm) to rooms housing broilers. The authors concluded that the application of this gas in a commercial broiler unit is unacceptable at the dosage studied because of increased mortality and reduced body gain and feed intake.…”
Section: Technical Papermentioning
confidence: 99%
“…NH 3 levels were measured only on specific days (15, 20, 28, 32, and 38 days), and the addition of O 3 caused a near-significant reduction (P ϭ 0.06) in NH 3 levels at 38 days (12.7 vs. 25.7 ppm) and total aerobe populations at 19 days (P ϭ 0.09). 23 As a powerful oxidizing agent, O 3 at high concentration levels may have potential to remove NH 3 through chemical reaction. This potential for NH 3 removal comes from the possible chemical reaction of O 3 and NH 3 .…”
Section: Technical Papermentioning
confidence: 99%
“…It is a sanification treatment that could improve air quality and reduce odors, levels of atmospheric ammonia, and bacterial load. Its use has been evaluated in many applications of the poultry industry [10,11,12] and also in intensive animal production units [13]. Its full effectiveness is not proved yet, and some possible issues regarding production and health—of both animals and human operators—are under evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…They could allow improving the air quality, limit odors, reduce levels of atmospheric ammonia and bacterial load [ 8 ]. The application of these treatments has been already investigated both for egg industry [ 9 , 10 , 11 ] and for egg production farms [ 12 ]. It has been proven that a concentration of ozone of at least 1 ppm, is necessary to perform an effective bactericidal procedure but, in the same time, its toxicity has been demonstrated both for animals and humans [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%